Efektivitas Media Pembelajaran E-Modul pada Mata Pelajaran Teknik Pemesinan Bubut di SMKS Dhuafa Padang - Fatriyanto, Fatriyanto; Waskito, Waskito; Syahril, Syahril; Kurniawan, Andre (Lembaga Yasin AlSys, 2024)
This study aims to examine the effectiveness of the use of e-module learning media on student learning outcomes in the subject of Lathe Machining Engineering class XI at SMKS Dhuafa Padang. The background of this research is the limited teaching materials and short learning time, which requires students to learn independently. The research method used is quasi-experimental with pretest-posttest control group design. The research sample consisted of 35 students of class XI Machining Engineering who were divided into experimental and control groups. Data were collected through learning outcome tests and analyzed using independent t-test. The results showed that: (1) the average pretest score of the experimental group was 54.77 and the control group was 61.67; (2) the average posttest score of the experimental group was 81.47 and the control group was 71.67; (3) there was a significant difference between the learning outcomes of the experimental and control groups (t = 0.549, p < 0.05). In conclusion, the use of e-modules is effective in improving student learning outcomes in Lathe Machining Engineering subjects. This study recommends the use of e-modules as an alternative learning media to improve student independence and learning outcomes.